THE EFFECT OF GREEN ACCOUNTING IMPLEMENTATION ON PROFITABILITY IN NON-CYCLICAL CONSUMER COMPANIES ON THE IDX IN 2020-2023 - Maduta, Santi Riskining Wahyu; Junjunan, Mochammad Ilyas; Nilamsari, Syalma Eka (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2025)
The rise of environmental pollution due to waste disposal requires companies to be more responsible for the impact of their operations. The implementation of green accounting is a strategic solution, as it helps companies manage environmental costs transparently and encourages sustainable practices. On the other hand, high profitability is needed to support this initiative while attracting investors who are increasingly concerned about environmental aspects. This study uses a quantitative approach with secondary data in the form of annual reports and sustainability of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2020-2023. Data was obtained through the website www.idx.co.id and selected using purposive sampling method with a total sample of 120 companies. The results showed that green accounting has an effect on profitability. This indicates that companies that implement green accounting well, such as responsible waste management, energy efficiency, and transparent environmental reporting, are able to utilize their assets more effectively in generating profits. Therefore, it can be seen that the implementation of good green accounting not only plays a role in preserving the environment, but also contributes to profitability.